The current practices of green computing approaches in Malaysia - Ahmaro I.Y.Y.; Bin Mohd Yusoff M.Z.; Abualkishik A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Internet; Internet telephony; Telecommuting; Voice/data communication systems; Algorithmic efficiencies; Current practices; Green computing; IT industry; Malaysia; Malaysian IT industry; Online surveys; Voice over Internet protocol; Internet protocols